2021
DOI: 10.1088/1361-6528/ac1bdc
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study to unravel the potential of using polysaccharides based organic-nanoparticles versus hybrid-nanoparticles for pesticide delivery

Abstract: To daze conventional pesticide release limitations, nanotechnology-mediated pesticide delivery using natural polymers has been actively investigated. However, the lack of information on what are the beneficial/non-beneficial aspects of using hybrid- and organic-nanoparticles (NP) and among the polysaccharides which are better suited concerning pesticide loading efficiency (PLE wt%), entrapment efficiency, and sustained pesticide release (SPR %) has prompted us to investigate this study. In this report, we syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Drug release kinetics for DOX-SS-NC was interpreted by fitting the release parameters in different release kinetics models using different equations using DD solver software (Section C6, Supporting Information), , and the best fitting models with R 2 closest to 1 were selected as an ideal drug release kinetics model (Table ). For drug release at 40 and 37 °C and at pH 7.4, the drug release parameters were best fitted in the Makoid-Banakar model having R 2 values 0.976 and 0.916, respectively (Figure S25a,c).…”
Section: Resultsmentioning
confidence: 99%
“…Drug release kinetics for DOX-SS-NC was interpreted by fitting the release parameters in different release kinetics models using different equations using DD solver software (Section C6, Supporting Information), , and the best fitting models with R 2 closest to 1 were selected as an ideal drug release kinetics model (Table ). For drug release at 40 and 37 °C and at pH 7.4, the drug release parameters were best fitted in the Makoid-Banakar model having R 2 values 0.976 and 0.916, respectively (Figure S25a,c).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, hybrid nanoherbicides can support strong traceability, targetability, and stimulus responsiveness qualities [32]. Due to their biocompatibility, biodegradability, natural abundance, and ease of functionalization, biomass-based hybrids made of lignin, xylan, starch, and cellulose have been investigated for their potential to encapsulate active molecules and can be used in the targeted assembling of herbicides [84]. Jiang et al [85] found that the fabrication of hybrid xylan-lignin nanoparticles gave nanomaterial amphiphilic characteristics and formed a core-shell structure.…”
Section: Nanoherbicides Based On Organic/inorganic (Hybrid) Nanomater...mentioning
confidence: 99%
“…However, more than 90% of the pesticides cannot accurately act on specific targets, and their effective utilization rate is low due to poor water dispersibility, dust drift, volatilization, evaporation, and degradation, which has led to serious environmental pollution [2][3][4]. With the rise of nanotechnology in the agricultural field, slow-and controlled-release pesticides have been rapidly developed [5][6][7]. Environmental stimulus-responsive systems, such as pH- [8][9][10], redox- [11,12], temperature- [13,14], enzyme- [15,16], and ultraviolet (UV)-light-responsive [17,18] materials have been developed for triggered pesticide release, which can improve the utilization rate of pesticides and reduce environmental pollution.…”
Section: Introductionmentioning
confidence: 99%